A comprehensive assessment of the method for producing biochar, its characterization, stability, and potential applications in regenerative economic sustainability – A review - Farah, Amalina; Abdul Syukor, Abd Razak; Krishnan, Santhana; A. W., Zularisam; Mohd, Nasrullah (Elsevier Ltd., 2022)
There is a rise of interest in various aspects of biochar derived from waste biomass to address the most pressing ecosystem challenges. This study contributes to understanding biochar's usage in the remediation of hazardous pollutants. The synthesis of biochar using a variety of different techniques has been explored. Numerous analysts have considered biochar as a strategy for enhancing their ability to remediate pollutants. Process factors are primarily responsible for determining biochar yield. Biochar-derived biomass is an exceptionally rich wellspring of carbon produced from biomass utilizing thermal combustion. Activating biochar is another field where biochar is increasingly used to remove specific contaminants. Closed-loop methods to produce biochar expand options. Distributed biochar manufacturing processes are an efficient method to develop businesses, manage waste, and increase resource proficiency in environmental applications. Additionally, this research discusses knowledge gaps and future directions in toxic pollutant remediation through biochar.